Effects of thermal-rate treatment and modification of Ce on the microstructure and properties of A356 alloys. Issue 2 (April 2021) - Zhang, Shuo; Bo, Lin; Wang, Lin; Hou, Yangbo; Zhao, Degang
Abstract: In this study, the effects of thermal-rate treatment (TRT) and modification of Ce on the microstructure and mechanical properties of A356 alloy were investigated. The results showed that the microstructure of A356 alloy was improved after TRT and modification of Ce. The α-Al was refined significantly and the eutectic Si transformed from needle-like shape to granular-like shape. When the content of Ce increased to 0.5%, the grain size of α-Al of A356 alloy began to increase and the dendrites became coarse. When the Ce content was 0.4%, the tensile strength and yield strength of A356 alloy were 183MPa and 124 MPa, respectively. The mechanism of (TRT+Ce) on the grain refinement of α-Al and modification of eutectic Si was discussed.